The hidden history of American fashion rediscovering 20th-century women designers - Deihl, Nancy (Bloomsbury Academic, 2018)
"This book is the first in-depth exploration of the revolutionary designers who defined American fashion in its emerging years and helped build an industry with global impact, yet have been largely forgotten. Focusing on female designers, the authors reclaim a place in history for the women who created not only for celebrities and socialites, but for millions of fashion-conscious customers across the United States"--Provided by publisher.